A nexus approach engaging water rights transfer for addressing water scarcity in energy and food production under uncertainty. (15th August 2022) - Zhang, Tianyuan; Tan, Qian; Zhang, Tong; Yang, Jian; Wang, Shuping
Abstract: Water rights transfer is significantly required for alleviating the ever-intensive water crisis, particularly for arid watersheds with abundant farmland and fossil fuels. However, focusing solely on the re-allocation of water rights and disregarding agricultural water saving potential imperil the security of Water-Energy-Food (WEF) nexus. Furthermore, randomness in water availability leads to water shortage risks and subsequent impact on the whole system. In this study, a risk-based optimization model (RWEF) was proposed to promote inter-sectoral water rights transfer through encouraging energy sector to invest in agricultural water-saving works and get paid back in water rights. Chance-constrained programming is incorporated to analyze the trade-offs between system benefits and water-shortage risks. The developed model was applied to the Inner Mongolia section of the Yellow River Basin, China to verify its effectiveness, considering different development levels of food and energy industries. Results indicated that 488 million m 3 of water could be transformed from agriculture to energy, without compromising agricultural production. The main recipients of transferred water rights would be traditional coal-based industries, while it would be difficult for thermal power and most modern coal chemical industries to participate. The construction of water-saving works would help safeguard agricultural production under risks. Compared against two alternative models without water rights transfer mechanism, the average benefit acquired from RWEF under varied water-shortage risks would be at least 68% higher. Particularly, when confronted with extreme water-shortage risk and increased production demands, RWEF would still be able to support agricultural and energy production, while the alternative models being incapable. Highlights: RWEF model is developed for investigating trans-sector water rights transfer under water-shortage risks. Energy sector invests in agricultural water-saving works and get paid back in water rights. Energy expansion plans with transferred water rights and cropping patterns with water-saving works are optimized. RWEF synergistically promotes the benefits of agriculture and energy sectors.